Pengaruh Karakteristik Individu dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan - Umban Jaya; Sri Sinta Rahmawati (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2022)
This study aims to see the effect of individual caracteristics and work environment on employee productivity of PT. Pratama Abadi Industri (JX) Sukabumi esspecially part Nosew UPS ( Upper Production Supporting). This study uses an associative quantitative approach using a questionnaire distributed to 100 samples with purposive sampling technique which has criteria as active employees of PT. Pratama Abadi Industri (JX) Sukabumi esspecially part of Nosew PT. Pratama Abadi Industri (JX). Testing instruments in research using validity and reliability tests, data analysis techniques using descriptive analysis, using classic assumption tests consisting of normality test, multicollinearity test, and heteroscedasticity test and multiple linear regression analysis. The results showed that: (1) individual caracteristics has a positive effect on employee productivity, as evidenced by the t value of -2,329 and the regression coefficient having a positive value of 0,255; (2) work environment has a positive effect on the employee productivity, as evidenced by the t value of 6,725 and the regression coefficient having a positive value of 0,635; and (3) individual caracteristics and work environment have a positive effect on on the employee productivity, as evidenced by the results of F count of 22,739 with a significance of 0.000. (4) The magnitude of the influence of individual caracteristics and work environment on employee productivity is evidenced by the Adjusted value R square of 0,319 indicating that the ability of the independent variable to explain the dependent variable is 31,9% and the remaining 68,9% applies to other variables outside this research model.